To determine which polynomial identity results from dividing \(x^2 - a^2\) by \(x - a\), we can use polynomial long division or factorization.
The expression \(x^2 - a^2\) can be factored as follows:
\[ x^2 - a^2 = (x - a)(x + a) \]
This shows that \(x^2 - a^2\) indeed equals \((x - a)(x + a)\).
Now, let's check the options:
- Option #1: \(x^2 - a^2 = (x - a)(x + a)\) - This is correct.
- Option #2: \(x^2 - a^2 = (x - a)(x - a)\) - This is incorrect.
- Option #3: \(x^2 - a^2 = (x + a)(x + a)\) - This is incorrect.
Thus, the correct answer is Option #1.